COMPARISON OF TCM-199 AND SOF MEDIA ON IN VITRO DEVELOPMENT OF OVINE PREIMPLANTATION EMBRYOS - RANGASAMY, S; PALANISAMY, A; SATHESHKUMAR, S; PRASAD, CH SRINIVASA; NAINAR, A MAHALINGA (The Indian Journal of Animal Reproduction, 2023)
The aim of the present study was to compare the effectiveness of two different media viz undefinedmedia (TCM-199) and semi defined (SOF) media for in vitro development of ovine preimplantationembryos. A total of 17 4 ovaries were sliced and 782 oocytes were recovered with a total recovery rateof 4.5 oocytes per ovary and cultureable oocytes recovery rate of 2. 7 oocytes per ovary. The presumptivezygotes derived from in vitro maturation and fertilization (IVM/IVF) were randomly subjected for two invitro culture (IVC) systems (TCM-199 and SOF), Statistical analysis revealed that highly significant(P>0.01) percentage of embryos reached morula after cleavage in SOF media (30.4±1 .14) than TCM~·-.199 (21.7±0.93). From this study, it was concluded that semi defined media like SOF support highrate of ovine morula development than undefined media like TCM-199 complex media due to aminoacids included in SOF media and a biphasic effect of bovine calf serum inhibiting the first cleavage andpromoting further morula and blastocyst development in TCM-199 media.
Keywords: ln vitro development; Ovine oocytes; TCM-199; SOF media